From Directions historical writing in the third century Hijri: genealogy - Sebti, Moneer Jehad Mohamed (Al-Adab Journal, 2020)
Genealogy: The significance of genealogy lies with Muslim Arabs, as represents the basis of honor and pride . Through genealogy the true lineage of people may be differentiate from the forged one (s). Genealogy is one of the distinguished sciences developed by Almighty God, were He said in his Holy Qura'an , "O mankind We created you from a single (pair) of a male and a female , and made you in to nations and tribes , that ye may know each other (not that ye may despise each other ) . Verily the most honored of you in the sight of Allah is ( he who is ) the most righteous of you. " And his saying ," It is He Who has created man from water : then has He established relationships of lineage and marriage : for thy Lord has power (over all things ) . "The lineage brings pride and a cause for strength, familiarity, love and communication. Depending on the importance of lineage and genealogy of the Arabs before and after Islam, it become a science among other Islamic sciences and took a significant portion in the historical writing. It became one of the distinguished trends of historical writing of the third century AH. History writer's narrators and genealogists played a great role in the writing of genealogy.